2020
DOI: 10.1080/1573062x.2020.1800760
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and statistical modelling of the solids accumulation rate in gully pots

Abstract: Gully pots are utilized for conveying runoff to drainage systems, as well as for reducing the system's solids loading by retaining suspended solids. However, the accumulation of solids in gully pots reduces their removal efficiency, leading to an increase in solids transport towards the drainage system. This article aims to identify the main drivers of the solids accumulation in gully pots and, thus the relevant processes for wash-off models. The solids accumulation rates in 407 gully pots were monitored withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Full information on the dimensions, accumulation periods and contributing drainage areas of the seven GPs sampled is provided in Table 1 . GPs investigated in this work have a volume of 80–104 L, which is similar to the UK design of 90 L (Butler and Memon 1999 ) and slightly larger than the Dutch design of 4–70 L (calculated using data from Post et al ( 2016 ) and Rietveld et al ( 2020b )). However, the Swedish, UK and Dutch designs are considerably smaller than the Swiss design of 250–450 L (Conradin 1989 ) and the Norwegian design of 790 L (Lindholm 2016 ).…”
Section: Methodsmentioning
confidence: 57%
“…Full information on the dimensions, accumulation periods and contributing drainage areas of the seven GPs sampled is provided in Table 1 . GPs investigated in this work have a volume of 80–104 L, which is similar to the UK design of 90 L (Butler and Memon 1999 ) and slightly larger than the Dutch design of 4–70 L (calculated using data from Post et al ( 2016 ) and Rietveld et al ( 2020b )). However, the Swedish, UK and Dutch designs are considerably smaller than the Swiss design of 250–450 L (Conradin 1989 ) and the Norwegian design of 790 L (Lindholm 2016 ).…”
Section: Methodsmentioning
confidence: 57%
“…Moreover, the drought even caused deciduous trees to drop their leaves in the summer of 2018, which has been recorded in the photographs taken during sampling. Rietveld, Clemens, and Langeveld (2020a) showed that the accumulation rate of solids in gully pots shows a maximum in terms of volume during the 'leaf abscission' phase, but Figure 5(b) shows that the 'leaf abscission' phase corresponds to the lowest solids loading. Therefore, the volume captured in the gully pot is not directly proportional to the mass inflow and the characteristics of the solids have to be taken into account, when the mass inflow is transformed into the volume captured in the gully pot.…”
Section: Particle Size Distributionmentioning
confidence: 99%
“…The composition of solids present and available for wash-off in urban areas depends on the characteristics of the area and local conditions (Xanthopoulos and Augustin 1992;Rietveld, Clemens, and Langeveld 2020a), and they originate from various sources, such as: traffic, atmosphere, construction activities, weathering of buildings, animal wastes, trash, de-icing materials and vegetation. Many of these sources have a seasonal character, in particular, the effect of vegetation (Pratt and Adams 1984;Ellis and Harrop 1984;Rietveld, Clemens, and Langeveld 2020a) and deicing (Simperler, Keckeis, and Ertl 2019). Street sweeping is generally regarded as a sink for solids present on streets (Sartor and Boyd 1972;Amato et al 2010;Hixon and Dymond 2018).…”
Section: Sources and Sinksmentioning
confidence: 99%
“…The WGS4.0 sensor nodes are intended to be installed within the street inlets to measure the water and dirt levels inside the inlets sludge containment and to estimate the urgency of cleaning them. The cause and impact of clogging on drainage performance has been explored thoroughly [18], [19] and spatiotemporal correlations among nearby street inlets have been shown to exist [20]. Among the proposed solutions is a passive system for estimating water levels in runoffs using RFID tags [21] and a zigbee-based WSN using acoustic sensors [22].…”
Section: A Detecting Clogged Storm Drainsmentioning
confidence: 99%